2019
DOI: 10.1039/c9sc01669d
|View full text |Cite
|
Sign up to set email alerts
|

Emergent supramolecular assembly properties of a recognition-encoded oligoester

Abstract: The sequences of oligomeric molecules equipped with interacting side-chains encode the threedimensional structure, the supramolecular assembly properties, and ultimately function. In an attempt to replicate the duplex forming properties of nucleic acids, an oligoester containing an alternating sequence of hydrogen bonding donor (D) and acceptor (A) residues was synthesised. Characterisation of assembly properties of the ADAD oligomer revealed a supramolecular architecture that resembles the kissing stem-loops … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
(39 reference statements)
1
16
0
Order By: Relevance
“… 12 The synthesis of oligomers that form duplexes has turned out to be a tractable problem, 13 46 and we have found that some of these compounds also fold and catalyze reactions in a manner reminiscent of nascent RNA function. 47 , 48 …”
Section: Introductionmentioning
confidence: 99%
“… 12 The synthesis of oligomers that form duplexes has turned out to be a tractable problem, 13 46 and we have found that some of these compounds also fold and catalyze reactions in a manner reminiscent of nascent RNA function. 47 , 48 …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Some of these synthetic systems also exhibit properties that resemble those found in biopolymers, such as substrate binding, self-assembly and catalysis. [21][22][23][24][25][26][27] One of the most important functional properties found in biomolecules is the ability of nucleic acid oligomers to template the synthesis of a specic sequence of another oligomer, either protein or nucleic acid. This process is the molecular basis of evolution and is directly related to the duplex structure formed by nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Indeed, some very significant progress in devising a synthetic "information chemistry" has been made in recent years, notably with the development of sequence-specific polymerisation (i.e. sequence-writing) methodologies and mass-spectrometric sequencing techniques, [6][7][8] information-transfer protocols, [9][10][11] and the use of small "reader-molecules" to recognise and report copolymer sequence-information. [12][13][14][15] Using the latter technique, we recently showed that highly sequence-dependent 1 H NMR complexation shifts are produced in the spectra of copolyimides based on 1,4,5,8-naphthalene tetracarboxylic diimide (NDI) on complexation of an aromatic "probe" molecule such as pyrene or perylene.…”
Section: Introductionmentioning
confidence: 99%